Loose Parts-Based Learning as a Strategy to Stimulate Early Childhood Creativity - Ita Fitriawati; I. Ismail (Manunggal Halim Jaya, 2026)
This study aims to analyze the implementation of loose parts-based learning as a strategy to stimulate early childhood creativity at Harapan Putra Kindergarten. The research employs a mixed-methods approach, using a quasi-experimental non-equivalent control group design to obtain quantitative data, as well as interviews with the principal, teachers, and parents as supporting qualitative data. The research subjects consisted of children aged 4–6 years, divided into an experimental group and a control group. Creativity was measured using an observation checklist based on the indicators of fluency, flexibility, originality, and elaboration. The results show that the experimental group experienced a higher increase in creativity scores compared to the control group. The average score of the experimental group increased from 59.40 in the pretest to 83.20 in the posttest, while the control group only improved from 60.10 to 69.30. The independent sample t-test results indicate a significance value of 0.000 < 0.05, demonstrating a statistically significant difference in creativity improvement between the two groups. The qualitative findings support these results, showing that loose parts-based learning enhances children’s enthusiasm, active exploration, and ability to collaborate with peers. Therefore, it can be concluded that loose parts-based learning is an effective and innovative strategy for stimulating early childhood creativity and supporting child-centered learning.